Transforming Educational Quality Through Strategic Financial Planning Management - Moh. Sugandi; Firman Khoerudin Khalik; Nunung Nurul Kamilah; Selvi Nurlita (DAAR EL-IDARAH: Journal of Islamic Education Management, 2026)
This study investigates the financial planning process at MTs Daruttawabin, focusing on the planning stage of madrasah financial management an aspect underexplored in Islamic education governance research. Using a qualitative approach through interviews, observation, and documentation analysis of RKAM and financial reports, the study finds that financial planning follows a sequential process of needs identification, budget drafting, and management coordination, yet is constrained by heavy dependency on a single funding source (BOS), limited stakeholder participation, and weak long-term needs mapping. These findings contribute theoretically to Islamic educational management by affirming the relevance of participatory and transparency-based planning models, while practically offering a basis for redesigning madrasah financial governance through funding diversification and institutionalization of long-term planning mechanisms.